Estudo demográfico e comparativo do manejo de elefantes asiáticos (Elephas maximus, Linnaeus 1758) sob cuidados humanos no Brasil - Schweizer, Marina Moraes (Universidade Federal de São Carlos, 2022)
The asian elephant is a species of herbivore mammal which is considered to be megafauna. For thousands of years the elephants are kept under human care. Despite the long history of elephants in captivity, there are still difficulties in keeping these animals under conditions that can foster well being and allow the animals to prosper. Zoo associations and international sanctuaries have developed documents as guidelines for their associates. In Brazil there is no such document available yet. The Asian elephants living in Brazil are distributed between many institutions. This work has the goal of putting together the information that these institutions have on their animals and to compare management strategies employed by each institution with the available literature. Overall, we did 305 hours of field work, visiting seven among the ten institutions housing Asian elephants. We collected data on the infrastructure of their enclosures, on the individuals themselves, their feeding and their managing. This work shows that Brazilian institutions are working towards the setpoints determined by the international guidelines, although we aren’t quite there yet. Finally, some changes are proposed so that the institutions can improve the welfare of their elephants and providing more opportunities for their animals to live fulfilling lives.
A study of the demography and a comparative assessment of management strategies of Asian elephants (Elephas maximus, Linnaeus 1758) under human care in Brazil.
Keywords: Bem-estar animal; Zoológico; Comportamento; Alimentação; Recinto; Animal welfare; Zoological garden; Behavior; Feeding; Enclosure; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::UTILIZACAO DOS ANIMAIS; CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL